2010
DOI: 10.1080/13603110802504945
|View full text |Cite
|
Sign up to set email alerts
|

Training young people as researchers to investigate engagement and disengagement in the middle years

Abstract: This paper reports on the first stage of a study that used Young People as Researchers to investigate the phenomenon of middle-year student engagement and disengagement. The first stage of the study focused on a two-day workshop that provided training for students and teachers from four secondary schools in conducting research in their schools. An overview of the three stages is presented and the workshop procedures and example activities for Stage 1 of the Young People as Researchers model are described. Furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 12 publications
(9 reference statements)
0
26
0
Order By: Relevance
“…A study that offers a useful description of the step-by-step process of using students as co-researchers is offered by Carrington, Bland, and Brady (2009). The research reported here has used some of the ideas presented in their article, in International Journal of Inclusive Education regards to organising students' training in a two-day workshop that was carried out at the university.…”
Section: The Workhopsmentioning
confidence: 97%
See 1 more Smart Citation
“…A study that offers a useful description of the step-by-step process of using students as co-researchers is offered by Carrington, Bland, and Brady (2009). The research reported here has used some of the ideas presented in their article, in International Journal of Inclusive Education regards to organising students' training in a two-day workshop that was carried out at the university.…”
Section: The Workhopsmentioning
confidence: 97%
“…Nevertheless, there are plenty of examples internationally where schools have involved students as researchers through projects to explore various aspects of school life (Ainscow and Kaplan 2005;Carrington, Bland, and Brady 2009;Fielding 2001;Goldrick 2008;Tangen 2009; Thomson and Gunter 2006). These accounts demonstrate that engaging with students' voices is not only feasible but that it can also provide a useful insight as to what is happening in schools, as well as helping to move practice forward.…”
Section: Introduction -Research With Studentsmentioning
confidence: 92%
“…Restrictive definitions of literacy (such as described earlier in the paper) alongside restrictive assessment and standardised testing procedures in schools that are still defined by written and/or verbal organisation and capability serve to reinforce a message that traditional forms of communication are what matters most when it comes to a child's ability to express themselves in an accepted way, when this is not the case. Children's ability to express themselves capably in a variety of forms and mediums is largely supported in educational research methodology literature (Carrington, Bland, & Brady, 2010;Gillett-Swan, 2013Kellett, 2010;Niemi, Kumpulainen, & Lipponen, 2015), yet is largely ignored in pedagogical literature. If the child's right to freedom of opinion and expression is to be realised, each of these barriers to educational transformation must be disrupted to enable voice-inclusive practice.…”
Section: Pedagogical Traditions: Teaching To the Middlementioning
confidence: 99%
“…Additional factors included atmospheric conditions such as temperature (both inside and outside), furniture, and facilities. This theme indicated that students did take into consideration how the physical learning environment related to their engagement (Carrington et al, 2010). Overall, student voice about engagement indicated that the students who participated in the various student-researcher investigations were committed to, and sought active participation in, their learning.…”
Section: Physical Learning Environmentmentioning
confidence: 99%
“…One way in which confidentiality was negotiated while also facilitating student voice in the process was that student-researchers chose their own pseudonyms. In addition, some of the expectations for the participatory project were covered in workshops to help the novice researchers understand key principles and practices of research (Carrington et al, 2010). Workshop One was designed as an important introduction to research in general and to develop a shared understanding of the research focus on student engagement.…”
Section: © Ucl Institute Of Education Press 2016mentioning
confidence: 99%